Band tailoring by annealing and current conduction of Co-doped ZnO transparent resistive switching memory. Issue 1 (February 2021) - Panda, Debashis; Simanjuntak, Firman Mangasa; Pradhan, Alaka; Gapsari, Femiana; Prodromakis, Themis
Abstract: The switching characteristics of ITO/Zn1-x Cox O/ITO transparent resistive random access memories were studied. 5 mol% cobalt doped ZnO resistive layer improves bipolar switching properties. In addition, the redshift in band energy caused by doping of cobalt (Co) was studied. The doped memory device also showed a change in band energy by 0.1 eV when subjected to annealing of 400 °C. Annealing below 400 °C temperature did not show any characteristic changes. The film morphology analysis suggested the increase in roughness with annealing temperature, which can be seen from FESEM and AFM images. In this study annealing and Co doping effect on ZnO based non-volatile memory device is presented. Moreover, transparent memory devices with 90% transmittance at 550 nm wavelength have been reported. At low field and high field region Schottky emission and ionic conduction are dominated respectively.